Hospitalization for varicella in Israel in the pre vaccination era - Marcus, Nufar; Hoffer, Vered; Shnitman, Nataly; Finkelstein, Yaron; Chodick, Gabriel; Garty, Ben Zion (Journal of Pediatric Infectious Diseases, 2006)
Although varicella is considered a common benign childhood infection, it accounts for significant morbidity and, in rare cases, may cause death. During the last years, a live attenuated vaccine is available, but has not been routinely incorporated into the vaccination program in Israel. In order to determine the magnitude of varicella complications and the epidemiology of the disease, we retrospectively studied records of 304 children with varicella hospitalized in a single medical center in Israel over a six-year period. Mean age of the patients was 2 years and 9 months (range: 2 weeks-21 years), and mean hospital stay was 4.5 days. Two hundred thirty-three patients (77%) were otherwise healthy and 71 (23%) had an underlying disease. The majority of children (n = 252, 83%) were hospitalized because of complications, mainly skin and soft tissue bacterial infections (n = 142, 47%), followed by pneumonia or pneumonitis (n = 56, 18%), gastrointestinal symptoms (n = 44, 14%), and central nervous system complications (n = 40, 13%), including febrile seizures (n = 25, 8%). Thirty-four children (11%) were immunocompromised and were hospitalized mainly for intravenous acyclovir treatment. There were no varicella-related deaths. Varicella continues to cause substantial morbidity and poses a significant economic burden in Israel. Further studies are needed to examine the cost-effectiveness of varicella vaccination in Israel.
Keywords: Varicella; hospitalization; vaccination